Design of Steel Structures [2nd ed. rev.] - Ram, K.S.Sai (New Delhi: Pearson, 2015)
This book on the design of steel structures uses the Limit State method and follows the latest BIS Code, IS 800:2007. With a perfect mix of theory and relevant applications, Design of Steel Structures discusses the most recent design methodologies in the subject, thus making it an excellent offering for students and practising engineers.
Keywords: Structural analysis; Building, Iron and steel